Biosynthesized ZnO Nanoparticles using Rivea Hypocrateriformis Pant Extract Assisted for Photocatalytic Activity in the Treatment of Wastewater - Murugesan Balaji; Pattulingam Rajesh; Sathasivam Kavica; Nagarajan Vignesh (Journal of Water and Environmental Nanotechnology)
These days, a material with antimicrobial and photocatalytic activity is highly needed due to the developing problem of water contamination by wastewater released from the expanding paper, ink, leather, and textile industries as well as provides with disease-causing pathogenic microorganisms. Zinc oxide (ZnO) nanoparticles (NPs) lend interesting qualities that make them a viable photocatalyst for removing hazardous pollutants, especially methylene blue dyes (MB dyes), from wastewater. Nanoparticles Synthesised by the Coprecipitate method and synthesized nanoparticles were characterized by UV visible spectroscopy showing a prominent peak at 350 nm conforming to the formation of Zinc Oxide nanoparticles, while FT-IR analysis shows the biomolecules responsible for the functional group involved in the formation of nanoparticles. The surface morphology was confirmed from the SEM analysis and EDX shows the elemental composition present in the prepared sample. XRD pattern confirmed the partial crystal spherical form and crystal nature of the particle. The potential of the Zinc Oxide catalyst to degrade Methylene Blue under sunlight, various concentrations of pH, and different catalytic dosages are investigated. In irradiation of time, the photocatalytic activity under sunlight absorption of dye took place by 93% over 165min. The catalyst improved the degradation of the methylene blue dye, and a higher pH led the dye to degrade more effectively. The recovered catalyst showed deterioration percentages for four cycles.